2020
DOI: 10.1038/s41525-020-00144-x
|View full text |Cite
|
Sign up to set email alerts
|

A three-year follow-up study evaluating clinical utility of exome sequencing and diagnostic potential of reanalysis

Abstract: Exome sequencing (ES) has become one of the important diagnostic tools in clinical genetics with a reported diagnostic rate of 25–58%. Many studies have illustrated the diagnostic and immediate clinical impact of ES. However, up to 75% of individuals remain undiagnosed and there is scarce evidence supporting clinical utility beyond a follow-up period of >1 year. This is a 3-year follow-up analysis to our previous publication by Mak et al. (NPJ Genom. Med. 3:19, 2018), to evaluate the long-term clinical util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 77 publications
3
70
0
Order By: Relevance
“…The discovery of gene‐disease and variant‐disease associations is continually growing necessitating regular reevaluation of unsolved exomes 48,49 . In line with previous studies demonstrating an improved diagnostic yield by systematic reanalysis of existing data, 48,50 we achieved a definitive diagnosis in two additional individuals (among 80 reanalyzed individuals with initial negative results). Beyond, reanalysis in our cohort lead to the identification of two novel candidate genes for NDDs highlighting the potential of subsequent reanalysis also for disease gene discovery 41,51 …”
Section: Discussionsupporting
confidence: 62%
“…The discovery of gene‐disease and variant‐disease associations is continually growing necessitating regular reevaluation of unsolved exomes 48,49 . In line with previous studies demonstrating an improved diagnostic yield by systematic reanalysis of existing data, 48,50 we achieved a definitive diagnosis in two additional individuals (among 80 reanalyzed individuals with initial negative results). Beyond, reanalysis in our cohort lead to the identification of two novel candidate genes for NDDs highlighting the potential of subsequent reanalysis also for disease gene discovery 41,51 …”
Section: Discussionsupporting
confidence: 62%
“…For the last category, it is expected that exome reanalysis would increase diagnostic yield. Based on previously published studies, exome reanalysis results in an increase in diagnostic yield of approximately 12%, with reported increases ranging from 5 to 26% [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Although the reported interval between initial analysis and reanalysis varies from 6 months to 7 years among reanalysis studies, the majority of reanalyses were performed at 1-to 2-year intervals [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Benefits Of Exome Reanalysismentioning
confidence: 99%
“…Ultimately, such efforts may result in changes to the clinical management of the patients and families. Several previous studies have demonstrated the clinical validity of exome reanalysis to increase the diagnostic yield [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and the American College of Medical Genetics and Genomics (ACMG) recently published a series of points to consider regarding the reevaluation and reanalysis of genomic test results at various levels [20]. While challenges remain, it is important for both ordering physicians and clinical laboratories to recognize the need for exome reanalysis as a routine clinical practice, given the evolving nature of the genomic field.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fogel et al (2014) reported a success rate of 73% (22/30) in diagnosing patients with sporadic cerebellar ataxia. Reanalysis of the undiagnosed exomes and coupling WES with other genetic approaches, such as mRNA sequencing and CNV detection, also increase WES’s diagnostic yield ( Deelen et al, 2019 ; Jalkh et al, 2019 ; Fung et al, 2020 ; Matalonga et al, 2020 ). CNVs are common in some SCD subtypes, e.g., SPG4 (OMIM # 182601) and SCA15 (OMIM # 606658; Depienne et al, 2007 ; Hsiao et al, 2017 ).…”
Section: Tools Used To Discover Scd Genes In the Pastmentioning
confidence: 99%
“…One study reported a rise of 7% in the diagnostic success rate upon reanalyzing the WES data of a cohort of SCD patients ( Ngo et al, 2020 ). Recent reports advocate for a periodic reanalysis of WES data ( Jalkh et al, 2019 ; Liu et al, 2019 ; Fung et al, 2020 ; Ngo et al, 2020 ). The 5-year cumulative increase in the diagnostic success rate upon WES data reanalysis ranges from 12 to 22% ( Liu et al, 2019 ).…”
Section: Tools Used To Discover Scd Genes In the Pastmentioning
confidence: 99%